Digital Transformation in Local Government: Enhancing Financial Transparency through the Regional Financial Information System (SIKD) - M. Rizki Maulidi; Zia Safira; Jihaan Nabila; Mariana Mariana; Rahmati, Rahmati (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
This study aims to analyze the implementation of the Regional Financial Information System (Sistem Informasi Keuangan Daerah, SIKD) in enhancing financial transparency in local governments during the digital era. Additionally, it explores the impact of digital advancements on accountability and financial reporting, including their effects on efficiency and report quality. The study also identifies various challenges faced by local governments in achieving financial transparency and provides strategic recommendations to address these obstacles. The research employs a qualitative approach using a literature review method. Data were collected from scientific journals, research reports, and relevant articles discussing the role of information technology in enhancing transparency, the challenges of its implementation, and strategies for optimization. The data were categorized into three main themes: the contribution of information technology to transparency, barriers to its adoption, and strategic steps for optimization. The findings indicate that the implementation of SIKD, as mandated by Government Regulation No. 56 of 2005, significantly supports transparency and accountability in local financial management by facilitating structured and systematic documentation, management, and reporting of financial data. Digital transformation positively impacts efficiency, accuracy, and the openness of local financial information. However, several challenges persist, such as resistance to transparency, a lack of technological expertise, and limited infrastructure. To overcome these obstacles, collaboration between governments and communities, improving human resource competencies, and developing technological infrastructure are strategic steps to ensure better transparency.